2013
DOI: 10.1089/acm.2011.0665
|View full text |Cite
|
Sign up to set email alerts
|

Auricular Acupressure for Pain Relief in Adolescents with Dysmenorrhea: A Placebo-Controlled Study

Abstract: Auricular acupressure relieves menstrual pain and distress in high-school adolescents. The findings may serve as a basis for using auricular acupressure to treat dysmenorrhea in adolescents. There was pain reduction with sham as well as with true acupoint acupressure, but the latter was significantly greater. The sham acupoint may not be used as a control for auricular acupoint and qualitative evaluation of dysmenorrhea should be added to the evaluation by SF-MPQ in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 36 publications
3
43
2
2
Order By: Relevance
“…This observation is consistent with previous studies [26, 28, 30]. Auricular acupressure combined with interactive Internet intervention was more effective than auricular acupressure alone in improving dysmenorrhea self-care.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This observation is consistent with previous studies [26, 28, 30]. Auricular acupressure combined with interactive Internet intervention was more effective than auricular acupressure alone in improving dysmenorrhea self-care.…”
Section: Discussionsupporting
confidence: 93%
“…Auricular acupressure can be used to treat the symptoms associated with primary dysmenorrhea, inhibit excessive production of prostaglandins, reduce excitability of the cerebral cortex, and regulate endocrine hormone secretion [25]. Many studies have demonstrating the beneficial effects of auricular stimulation on menstrual pain and distress [2630]. …”
Section: Introductionmentioning
confidence: 99%
“…The French version of EA is based on the assumption that the human body is represented in the outer ear as an inverted fetus and that there is a relationship between distinctive anatomical sites and specific points in the ear 1 . Previous studies showed that EA is effective to reduce pain as a single treatment 2 - 5 or as an adjuvant of other types of treatment 6 - 9 . For instance, EA was better than sham EA to reduce pain in adolescents with dysmenorrhea 5 and in older adults immediately after a hip fracture 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that EA is effective to reduce pain as a single treatment 2 - 5 or as an adjuvant of other types of treatment 6 - 9 . For instance, EA was better than sham EA to reduce pain in adolescents with dysmenorrhea 5 and in older adults immediately after a hip fracture 3 . However, in most of EA studies, participants either received several sessions of EA or kept the needles inserted for hours or even days.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic proposals which are being increasingly used by qualified professional derive from TCM, such as acupuncture, acupressure and auricular acupuncture. Studies 21,25 have shown improved pain in women suffering from primary dysmenorrhea. The study by Yu et al 20 reports that immediate acupuncture effect on Sanyinjiao point (SP6) provides immediate menstrual flow improvement.…”
Section: Participantsmentioning
confidence: 99%